Cohort profile: the Welsh Geriatric Registrar-Led Research Network (WeGeN): rationale, design and description. Issue 2 (14th February 2017) - Jelley, Benjamin; Long, Sara; Butler, John; Hewitt, Jonathan
Abstract : Purpose: Medical trainees are required to undertake audit and quality improvement projects. They must also have an understanding of the principles of research and are encouraged to participate in research projects. However, the constraints of time, a lack of formal training and rotation between different training posts create barriers to audit cycle completion and pursuing research. This leads to trainees being reluctant to undertake research, facilitates poor quality research and risks incomplete audit. Participants: The Welsh Geriatricians Network (WeGeN) has been created with the aims of facilitating collaborative, trainee-led research within Geriatric Medicine in Wales, promoting research engagement and improving the research evidence base for older patients. By coordinating collaborative research projects across different sites within Wales, trainees continue existing projects at new sites, allowing completion of projects and establishing the long-term infrastructure and experienced personnel needed for high-quality research data to be gathered. Findings: WeGeN has facilitated 4 national audits, all of which are intended for peer review publication. The first project considers the service provision for the older person in the emergency department, the second Parkinson's disease, the third reviews delirium management and the fourth project considers epidemiology of surgical disease in older people. Future plans: The objective of this project is to further establish and develop WeGeN as a group which facilitates high-quality research and provides the opportunity for geriatric trainees to engage in research activity. It is anticipated that the establishment of this research platform will provide a blueprint for the development of other such networks in the UK and beyond.